The Effectiveness of Neuroscience to Improve Teacher Pedagogic Competence: Systematic Literature Review - Ana Maria Heni; Ade Iriani; Bambang Ismanto (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2023)
Teaching is a profession, so it is required to be professional. The meaning is that the teacher must have a special quality that has been determined. Even so, it cannot be denied that there are still many teachers who do not meet these qualifications. Therefore, teachers need to improve their quality or competence by participating in neuroscience training. The purpose of this study was to analyze neuroscience education training can improve teacher competence, especially pedagogical competence. This type of research is SLR. The data in this study are from both international and national journals. The results of this study say that: neuroscience training can help teachers understand the characteristics of students in various aspects. By understanding neuroscience, teachers become masters of learning theory and educational principles of learning. By understanding neuroscience, teachers become able to facilitate the development of student's potential. Based on these results, it can be concluded that neuroscience education training can improve teacher pedagogical competence.